Towards a cross-modal perspective of emotional perception in social anxiety: review and future directions - Peschard, Virginie; Maurage, Pierre; Philippot, Pierre (Frontiers in Human Neuroscience, 2014)
The excessive fear of being negatively evaluated constitutes a central component of social anxiety. Models posit that selective attention to threat and biased interpretations of ambiguous stimuli contribute to the maintenance of this psychopathology. There is strong support for the existence of processing biases but most of the available evidence comes from face research. Emotions are, however, not only conveyed through facial cues, but also through other channels, such as vocal and postural cues. These non-facial cues have yet received much less attention. We therefore plead for a cross-modal investigation of biases in social anxiety. We argue that the inclusion of new modalities may be an efficient research tool to (1) address the specificity or generalizability of these biases, (2) offer an insight into the potential influence of social anxiety on cross-modal processes, (3) operationalize emotional ambiguity by manipulating cross-modal emotional congruency, (4) inform the debate about the role of top-down and bottom-up factors in biasing attention, and (5) probe the cross-modal generalizability of cognitive training. Theoretical and clinical implications as well as potential fruitful avenues for research are discussed.